Pengaruh Penggunaan Puzzle Gambar dalam Meningkatkan Kemampuan Menulis Cerita pada Siswa Kelas IV di SDN 09 Talang Babungo - Sababalat, Admyssa Citra Buana; Sitompul, Dina Lestari (TSAQOFAH, 2024)
Making picture puzzle media aims to make fourth grade students more enthusiastic and not feel bored when learning to write narrative stories. This is because currently, the learning methods used are less interesting and students are less enthusiastic. In this research, we want to ensure that the use of picture puzzle media is effective and appropriate. The development process follows the ADDIE research model. We use a questionnaire to assess the suitability of this media through the opinions of material experts, media experts and teachers. The results of this research indicate that the picture puzzle media developed is suitable for use by class IV students at SDN 09 Talang Babungo to learn to write narrative stories. Therefore, the use of this media is expected to improve students' writing skills.